Candradimuka Anom Project: Strategi Peningkatan Domain Partisipasi dan Kepemimpinan dalam Indeks Pembangunan Pemuda Jawa Tengah - Radite Ranggi Ananta; Daei Aljanni; Abi Umaroh; Syifa Yustiana; Rizki Anugrah Robby (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the Candradimuka Anom Project as an innovative model to strengthen the Youth Development Index (IPP) in Central Java, with a focus on Domain 4: Participation and Leadership. The study is motivated by the low performance of youth organizational participation, social engagement, and leadership indicators, which remain below national targets. Using a descriptive qualitative approach, the research relies on document analysis, including the project proposal of PW IPM Central Java, national and provincial IPP data, and relevant youth development literature. The findings show that the program is implemented through sequential stages consisting of recruitment, online bootcamp, leadership camp, and social action projects. These stages are reinforced by collaboration among multiple stakeholders, such as local governments, youth organizations, universities, and community groups. IPM plays a strategic role in mobilizing student networks, providing institutional legitimacy, and maintaining program sustainability. The intervention is projected to measurably enhance social participation, organizational involvement, and youth confidence in public expression. Consequently, the Anom Project contributes to improving Central Java.